Integrated Nutrient Management Practices in Agroforestry - Sarvade, S.; Agrawal, S. B.; Bajpai, R.; Thakur, R. K.; Shrivastava, Atul (International Journal of Bio-resource and Stress Management, 2025)
Agroforestry is a transformative land-use strategy that integrates trees, crops, and livestock into cohesive systems, promoting sustainability through enhanced environmental, economic, and social outcomes. By blending diverse plant and animal species, agroforestry systems foster ecological balance and resilience, supporting biodiversity, soil health, and water conservation. Proper management of these resources, particularly soil, water, and biodiversity, is crucial for maximizing both ecological and economic benefits. Effective soil management enhances nutrient cycling and improves soil structure, ensuring long-term productivity. Integrated Nutrient Management (INM) combines organic and inorganic fertilizers to boost soil fertility and plant health, promoting growth while maintaining environmental integrity. The success of INM relies on factors such as soil characteristics, climate, and plant species, all influencing its effectiveness in agroforestry systems. These variables impact nutrient dynamics, necessitating adaptive management practices. Moreover, socio-economic factors such as land tenure, farmer knowledge, and market access influence the adoption and success of INM practices. Therefore, understanding the local context and incorporating these elements into agroforestry planning is essential for maximizing its benefits. The integration of efficient resource management with INM in agroforestry systems is vital for achieving long-term sustainability, ensuring food security, and promoting environmental conservation. Agroforestry optimizes nutrient use and promotes plant synergy, offering sustainable solutions to global challenges like climate change and food security.